2017
DOI: 10.4317/medoral.22128
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of RANKL and OPG, and the RANKL/OPG ratio in bisphosphonate-related osteonecrosis of the jaw: Are they useful biomarkers for the advanced stages of osteonecrosis?

Abstract: BackgroundWe determined whether serum levels of Receptor Activator for Nuclear Factor κ B Ligand (RANKL), Osteoprotegerin (OPG), and the RANKL/OPG ratio could be useful biomarkers for the severity of oral lesions in bisphosphonate-related osteonecrosis of the jaw (BRONJ).Material and MethodsA case-control study in which Group 1 consisted of 41 patients with BRONJ due to intravenous bisphosphonates, and Group 2 consisted of 44 healthy control cases. The plasma levels of RANKL and OPG were analyzed by an ELISA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Emerging evidences showed genetic association of diverse genes dysregulation with BRONJ7-9, suggesting that altered gene expressions might be potential biomarkers for BRONJ diagnosis. In addition, since BRONJ is closely related with bone metabolic disorders, bone turnover markers have been emerging to support diagnosis of BRONJ10-13. Nevertheless, inconsistent diagnostic performances were observed in various researches and no approved clinical guide has been established to manage BRONJ.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidences showed genetic association of diverse genes dysregulation with BRONJ7-9, suggesting that altered gene expressions might be potential biomarkers for BRONJ diagnosis. In addition, since BRONJ is closely related with bone metabolic disorders, bone turnover markers have been emerging to support diagnosis of BRONJ10-13. Nevertheless, inconsistent diagnostic performances were observed in various researches and no approved clinical guide has been established to manage BRONJ.…”
Section: Introductionmentioning
confidence: 99%
“…their apoptosis, inhibiting bone resorption by depleting mature osteoclasts 11 . However, two studies 1,28 showed that the serum levels of RANKL and OPG and the RANKL/OPG ratio were not valuable biomarkers to determine the severity of oral lesions in MRONJ patients.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Medication-related osteonecrosis of the jaw (MRONJ) is a severe complication that can occur in patients who have been treated with antiresorptive medication 1 . Bisphosphonate (BP) medications are the most frequently used class of anti-resorptive drugs for the treatment of bone disorders such as osteoporosis and cancer-associated skeletal complications 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations